EFFICACY OF SPECTRAL CT IMAGING IN DIFFERENTIATING RENAL STONES - Mohammed Mousa Altharwy, Moudy Abdullah Al Salamah, Muath Abdullah Alzeer, Faisal Manwer Almutairi, Khulud Mohammed Aldawsari, Hammud Abdulrahman Alrajeh,,; Mohammed Hamoud Hulayyil Alharbi, Abdulwahab Ali Aljobran, Idris Ali Idris Sumayli, (Chelonian Research Foundation, 2022)
Imaging of kidney stones is a crucial diagnostic technique and the first step in determining the appropriate treatment approaches for managing kidney stones. The guidelines from the American College of Radiology, American Urological Association, and European Association of Urology vary in their recommendations for the best first imaging method to assess patients with suspected obstructive nephrolithiasis. The use of noncontrast CT scans of the abdomen and pelvis consistently yields the most precise diagnosis, however it does expose patients to ionizing radiation. Historically, ultrasonography has shown a reduced sensitivity and specificity compared to CT scans, although it does not need the use of radiation. Nevertheless, a randomized controlled research revealed that these imaging modalities exhibited comparable diagnostic accuracy when used in the emergency room. Both techniques provide benefits and drawbacks. Kidney, ureter, bladder (KUB) plain film radiography is most beneficial for assessing the increase in size of stones in individuals with a history of stone illness, but it is less effective in diagnosing acute stones. MRI has the potential for radiation-free 3D imaging, but it is expensive and presently has limitations in seeing stones. Anticipated advancements will improve the capabilities of each imaging technique used to assess and treat kidney stones in the coming years. An approach that has been suggested for imaging individuals, who have acute stones, taking into account the existing recommendations and a randomized controlled study, might be helpful for doctors. Keywords: